ANALISIS REALISASI ANGGARAN PENDAPATAN DAN BELANJA DAERAH PADA PEMERINTAHAN KOTA PONTIANAK TAHUN ANGGARAN 2010 - B51109038, ARDI PRATAMA (Jurnal KIAFE, 2013)
This Research is motivated that the budget was very influential in government administration, both central and local government. Local budget and APBD is the main policy instrument for local governments and is a tool used to evaluate or monitor the financial condition and operational implementation of programs and activities of the government. Therefore it is an issue in study is how the realization of revenue and expenditure budget Pontianak City. While the purpose of this study was to determine the actual revenues and expenditures that occur on Pontianak City. Methods used in this research is descriptive method through case study with data collection by observation, interview, and documentation. Whereas data used are secondary data derived from Pontianak City administration report on accountabilityof budget revenue and expenditures for fiscal year 2010. Based on the results of research and analysis of the realization of revenue and expenditure budget Pontianak City. It can be seen that the apparatus in Pontianak City already perform tasks in creating and realizing maximum revenue and expenditure budget in Pontianak City. Although there are still some shortcoming because of constraints as budget constraints have, still less aware of the public to participate in local development, as well as the weakness of its human resources so that still needs a lot of improvement of various sectors. Keyword : Revenue, Expenditure, Budget, Realization